2015
DOI: 10.1111/cod.12487
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to chlorhexidine in a tertiary dermatology clinic in Denmark

Abstract: The prevalence of chlorhexidine contact allergy does not seem to be higher in Denmark than in other European countries. Patch testing with both chlorhexidine diacetate and chlorhexidine digluconate may be beneficial. Testing for immediate-type allergy in patients with a positive patch test reaction to chlorhexidine is recommended. Chlorhexidine-containing products used in the healthcare setting and in cosmetics are potential causes of sensitization and allergy. Re-exposure is common, highlighting the fact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…This polysensitization is not without any consequence since it constraints antiseptic use especially for their general use and for surgical site. In addition, these three components are also wellknown preservatives in drugs and cosmetics and thus limit their prescription …”
Section: Discussionmentioning
confidence: 99%
“…This polysensitization is not without any consequence since it constraints antiseptic use especially for their general use and for surgical site. In addition, these three components are also wellknown preservatives in drugs and cosmetics and thus limit their prescription …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 38 positive reactions in 3716 patients tested with chlorhexidine digluconate were observed, and it is therefore considered to be a relatively rare allergen (standardized prevalence 1.5%, 95%CI: 1.1-1.9%), although some reactions may have been missed. Indeed, Opstrup et al (38) recently investigated chlorhexidine contact allergy in Denmark, and detected a prevalence of 1.0%; they suggested that chlorhexidine diacetate should also be tested.…”
Section: The Allergensmentioning
confidence: 99%
“…In Europe, one of the most widely employed antiseptics is chlorhexidine digluconate, both in aqueous and alcoholic solution . Allergic contact dermatitis (ACD) to chlorhexidine is fairly common in adults, with a prevalence of up to 1%, but it is quite rare in pediatric population . We report 4 cases of ACD to chlorhexidine in pediatric patients diagnosed in our department between May and November 2018.…”
mentioning
confidence: 92%
“…The different commercial formulations of this antiseptic must be taken into account, as some regularly used excipients, such as benzyl alcohol, which can also cause ACD . Furthermore, we must inform parents that chlorhexidine is not only present in antiseptic products but also as a component of cosmetics . Last but not least, it is imperative to rule out immediate hypersensitivity reactions, as even mild cases of ACD can indicate a potential risk of acute hypersensitivity reactions following successive exposures to chlorhexidine …”
mentioning
confidence: 99%